2002
DOI: 10.1002/cne.10300
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of thyrotropin‐releasing hormone (TRH) immunoreactivity in the brain of the zebrafish (Danio rerio)

Abstract: The distribution of thyrotropin-releasing hormone (TRH) in the brain of the adult zebrafish was studied with immunohistochemical techniques. In the telencephalon, abundant TRH-immunoreactive (TRHir) neurons were observed in the central, ventral, and supra- and postcommissural regions of the ventral telencephalic area. In the diencephalon, TRHir neurons were observed in the anterior parvocellular preoptic nucleus, the suprachiasmatic nucleus, the lateral hypothalamic nucleus, the rostral parts of the anterior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
64
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 91 publications
14
64
0
Order By: Relevance
“…Thus, in untreated animals TRHir material was detectable in nerve fibers and terminals, but the cell bodies were only weakly stained or did not stain at all [Tsuruo et al, 1987[Tsuruo et al, , 1988aJózsa et al, 1988]. However, in recent studies in different anamniotes wide distribution patterns for TRH were described that included nicely stained cell bodies and in none of these studies colchicines was used [Lamacz et al, 1989;Miranda and Affanni, 2000;Díaz et al, 2001Díaz et al, , 2002De Andrés et al, 2002;Teijido et al, 2002]. In our study, we have used one animal of each species with colchicine pretreatment as controls and have observed that, at least in urodeles, the same immunoreactive cell groups are observed for each species with only a slight improvement of the intensity of the reaction; a result that contrasts with the situation found in amniotes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in untreated animals TRHir material was detectable in nerve fibers and terminals, but the cell bodies were only weakly stained or did not stain at all [Tsuruo et al, 1987[Tsuruo et al, , 1988aJózsa et al, 1988]. However, in recent studies in different anamniotes wide distribution patterns for TRH were described that included nicely stained cell bodies and in none of these studies colchicines was used [Lamacz et al, 1989;Miranda and Affanni, 2000;Díaz et al, 2001Díaz et al, , 2002De Andrés et al, 2002;Teijido et al, 2002]. In our study, we have used one animal of each species with colchicine pretreatment as controls and have observed that, at least in urodeles, the same immunoreactive cell groups are observed for each species with only a slight improvement of the intensity of the reaction; a result that contrasts with the situation found in amniotes.…”
Section: Discussionmentioning
confidence: 99%
“…In general, TRH was primarily detected in neurons of the preoptic area and hypothalamus, although the presence of TRH in neurons of other brain regions has also been reported [Matz and Takahashi, 1994;Díaz et al, 2001Díaz et al, , 2002Teijido et al, 2002].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…4A-C, arrowheads). The expression of trh in zebrafish has only been analyzed in adult brain (Diaz et al, 2002). In 76 hpf forebrain, trh is expressed in the preoptic region in a domain close to the anterior commissure.…”
Section: Arnt2mentioning
confidence: 99%
“…Thyroid follicles (the analog of the human thyroid gland) first produce T4 by 3 days post fertilization (dpf) (16), and substantial changes in tissue levels of T4 first occur by 5 dpf (17). TRH-producing cells are widely distributed in the zebrafish brain, including in the diencephalon, where thyrotropin-releasing hormone-containing (TRH-containing) fibers project to the adenohypophysis (18). Importantly, hormone levels can be easily manipulated in the zebrafish embryo, and thyrotropes can be tracked in real time, facilitating the analysis of HPT axis development under hyperthyroid conditions.…”
Section: Introductionmentioning
confidence: 99%